Ischemic Optic Neuropathy Secondary to Intravascular Lymphoma. Issue 3 (September 2019) - Dinkin, Marc; Lavi, Ehud; Winterkorn, Jacqueline; Oliveira, Cristiano; Merkler, Alexander E.
Abstract : Background: To describe a case of optic neuropathy associated with intravascular lymphoma (IVL). Methods: Case report and review of the literature. Results: A case of asymmetric binocular vision loss is described, preceded by transient vision loss. Associated optic perineural enhancement and enhancing and diffusion-positive cortical lesions were observed on magnetic resonance imaging. Biopsy of the cerebellum revealed exclusively intraluminal neoplastic B-cells consistent with IVL. Conclusions: Patients with IVL may rarely present with optic nerve involvement, presumably due to small vessel occlusion. The presentation may mimic features of anterior ischemic optic neuropathy including an acute onset and disc edema. Although optic nerve enhancement and associated white matter lesions may suggest optic neuritis, enhancement of the optic nerve sheath, as in this case, has a wide differential diagnosis, which includes giant cell arteritis. IVL should be considered in atypical cases of optic neuropathy accompanied by enhancing, diffusion-positive brain lesions that are not within a specific vascular territory.